2011
DOI: 10.1186/1471-2210-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of TRPV1 receptor ligands against nicotine-induced depression-like behaviors

Abstract: BackgroundThe contributions of brain cannabinoid (CB) receptors, typically CB1 (CB type 1) receptors, to the behavioral effects of nicotine (NC) have been reported to involve brain transient receptor potential vanilloid 1 (TRPV1) receptors, and the activation of candidate endogenous TRPV1 ligands is expected to be therapeutically effective. In the present study, the effects of TRPV1 ligands with or without affinity for CB1 receptors were examined on NC-induced depression-like behavioral alterations in a mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 57 publications
1
28
0
1
Order By: Relevance
“…These effects include antinociception (Aceto et al 1983), sedative and analgesic effect (Mattila et al 1968), alterations in cognition (Levin and Simon 1998) and memory (Zarrindast et al 1996), convulsions and seizure induction (Damaj et al 1999), and antidepression-like effect (Hayase 2011;Mineur and Picciotto 2010;Vieyra-Reyes et al 2008) in experimental animals. Animal studies have demonstrated that both acute and chronic administration of nicotine, without affecting locomotor behavior, exerted antidepressant-like effects in rodent models of depression such as the learned helplessness and forced swimming test (Djurić et al 1999;Tizabi et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…These effects include antinociception (Aceto et al 1983), sedative and analgesic effect (Mattila et al 1968), alterations in cognition (Levin and Simon 1998) and memory (Zarrindast et al 1996), convulsions and seizure induction (Damaj et al 1999), and antidepression-like effect (Hayase 2011;Mineur and Picciotto 2010;Vieyra-Reyes et al 2008) in experimental animals. Animal studies have demonstrated that both acute and chronic administration of nicotine, without affecting locomotor behavior, exerted antidepressant-like effects in rodent models of depression such as the learned helplessness and forced swimming test (Djurić et al 1999;Tizabi et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Intraprefrontal cortex or intraperitoneal (i.p.) administration of TRPV1 antagonist induces anxiolytic-like effects (Aguiar et al, 2009;Kasckow et al, 2004), and in preclinical models of depression-like behaviors induced by nicotine or immobilization stress, TRPV1 agonists show antidepressant-like effects in both the forced swimming and tail suspension tests (Hayase, 2011). Moreover, upregulation of TRPV1 in the dorsal root ganglion, spinal cord, and sciatic nerve through mitogen-activated protein kinase pathways after chronic morphine treatment contributed to morphine tolerance in rats (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…GABAergic, dopaminergic and serotonergic terminals are additional purported candidates to be modulated by TRPV 1 Rs, as central TRPV 1 Rs are implicated in mood disorders, anxiety, panic responses, depression and psychosis Chahl, 2011;Hayase, 2011;Casarotto et al, 2012;Moreira et al, 2012, Micale et al, 2013). Yet no direct presynaptic TRPV 1 R modulation of dopamine and GABA release has been observed so far in the adult rodent brain (see Table 1), while to our knowledge, presynaptic TRPV 1 R modulation of serotonergic terminals in the brain has never been looked for.…”
Section: Introductionmentioning
confidence: 99%